Dynamic Behaviors of an SEIR Epidemic Model in a Periodic Environment with Impulse Vaccination - Mei Yan; Zhongyi Xiang (Discrete Dynamics in Nature and Society)
We consider a nonautonomous SEIR endemic model with saturation incidence concerning pulse vaccination. By applying Floquet theory and the comparison theorem of impulsive differential equations, a threshold parameter which determines the extinction or persistence of the disease is presented. Finally, numerical simulations are given to illustrate the main theoretical results and it shows that pulse vaccination plays a key role in the disease control.